2003
DOI: 10.1165/rcmb.2002-0100oc
|View full text |Cite
|
Sign up to set email alerts
|

Increased Susceptibility to RSV Infection by Exposure to Inhaled Diesel Engine Emissions

Abstract: Although epidemiologic data strongly suggest a role for inhaled environmental pollutants in modulating the susceptibility to respiratory infection in humans, the underlying cellular and molecular mechanisms have not been well studied in experimental systems. The current study assessed the impact of inhaled diesel engine emissions (DEE) on the host response in vivo to a common pediatric respiratory pathogen, respiratory syncytial virus (RSV). Using a relatively resistant mouse model of RSV infection, prior expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
123
2
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(134 citation statements)
references
References 45 publications
7
123
2
2
Order By: Relevance
“…Studies indicate that virus-induced inflammation in the upper and lower respiratory tract may be exacerbated by concurrent exposure to low levels of diesel exhaust particulate matter, nitrogen dioxide and ozone commonly encountered in indoor and outdoor environments [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicate that virus-induced inflammation in the upper and lower respiratory tract may be exacerbated by concurrent exposure to low levels of diesel exhaust particulate matter, nitrogen dioxide and ozone commonly encountered in indoor and outdoor environments [51,52].…”
Section: Discussionmentioning
confidence: 99%
“…A syringe containing inoculant was expelled into the trachea followed by multiple injections of air to facilitate dispersion of inoculant into the lung periphery. Mice usually recovered within 5 min and resumed normal eating and grooming activities (26,27). Sterile medium (100 l/mouse) was used as control.…”
Section: Mouse Model Of Rsv Infectionmentioning
confidence: 99%
“…instillations of 0.6 ml of PBS into the right lung using a fine catheter tied to the right main bronchus, and the samples were pooled for each animal. The BALF was processed, and the total and differential cells were counted as described elsewhere (26,27). The remaining lung tissues were then used for histopathological and molecular studies as described below.…”
Section: Cell Counts In Balfmentioning
confidence: 99%
“…Accordingly, experimental studies investigating the impacts of DEP on responses to respiratory viral infection are sparse and are typically in vitro in nature, 12 , 13 or involve animal models of long‐term exposure to DE 14 , 15 , 16 . Furthermore, such studies usually entail exposing test animals to DE prior to infection to test the effects of exposure on susceptibility to infection 14 , 15 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, such studies usually entail exposing test animals to DE prior to infection to test the effects of exposure on susceptibility to infection 14 , 15 , 16 . Such studies have shown that exposure to DE results in increased susceptibility to respiratory viral infection, 14 , 15 , 16 higher viral replication, 15 increased pulmonary inflammation, 14 , 16 lower interferon levels 15 , 17 and up‐regulation of Toll‐like receptor 3 (TLR3) receptor expression and signalling 16 in mice.…”
Section: Introductionmentioning
confidence: 99%